The payment to keep me emotionally positive and physically productive. Business practice, underutilized, controversial and indispensable (Ingeniería, Sostenibilidad y Sociedad, 2024)
This expositional work has been carried out, seeking awareness regarding the salary aspect in companies and the psychological consequences of poor treatment between the company and results. The treatment of human talent, often erroneous and incomplete, is desired to be mitigated with money, through a salary that is labeled as sufficient. This research, broadly speaking, aims to demonstrate the consequences of an unfair salary on the worker themselves and on productivity.
Keywords: Affectation; salary; human resources; business success